Improving the wear resistance of heavy-duty elements in tribomechanical systems by a combined laser-thermochemical processing method - Kindrachuk, Myroslav; Dukhota, Oleksandr; Тіsov Oleksandr; Korbut, Evgen; Yurchuk, Alina; Kharchenko, Volodymyr; Naumenko, Nila (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports an analysis of the state of tribological support in the aviation industry. The use of surface strengthening technologies to extend the resource of friction node parts has been prioritized. Modern combined technologies of nitriding and laser treatment of steel surfaces have been reviewed. The mechanism has been elucidated that damages steel 30H2NVFA in the jackscrew actuator of transport aircraft flaps, which occurs due to insufficient surface hardness of the material after a generally accepted heat treatment. Auger electron spectroscopy analysis revealed a high concentration of oxygen on the surface: up to 41.4 at. %; the friction surface carbonation has been detected, especially significant at the surface of the pitting damage. A comprehensive technology of surface strengthening by nitriding+laser selective hardening has been suggested. The radiation power was 1 KW, the diameter of the focus spot was 2.5 mm, and the pitch between the focus spot centers was 2.5 mm. The total area of laser processing was 70 %. The steel temperature exceeded Ас3 and corresponded to the hardening temperature range. The depth of the nitrided layer increased to 400 µm, the maximum hardness on the surface was 1,350–1,380 HV0.2. The formation of a solid nitrided layer with a thickness of 200‒250 µm was observed, as well as a transition zone composed of column-shaped iron nitrides, which are introduced into the matrix material. As a result, a sharp gradient in the mechanical properties disappears. The tests confirmed that the wear resistance of the comprehensively treated surface was 2.1 times higher under dry friction conditions, and 4.5 times higher when lubricated with the "Era" grease (RF), compared with the 30H2NVFA steel nitrided by the conventional technology. In addition, there was no fragile destruction of the surface; the interaction with oxygen reduced significantly